2020
DOI: 10.3390/ijerph17155312
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sleep Quality is Associated with Personal and Parenting Weight-Related Behaviors

Abstract: Mothers of young children tend to report poor-quality sleep, yet little is known about links between maternal sleep quality and weight-related behaviors and parenting practices. Thus, mothers of preschoolers completed an online cross-sectional survey assessing their sleep, physical activity, dietary behaviors, eating styles, child feeding practices, family meal behaviors, and health parameters. Comparisons by sleep quality using the Pittsburgh Sleep Quality Index item (i.e., very bad/bad, n = 87; fair, n = 255… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…68 A cross-sectional secondary analysis conducted by Blumfield et al 69 in a diverse sample of New York residents found that poor sleep quality was associated with disinhibited eating scores ( B = 0.20; 95% CI, 0.09-0.30, p < .001) and further, sleep quality was indirectly related to increased BMI through higher disinhibition scores ( B = 0.13; 95% CI, 0.06-0.21, p = .001). Eck et al 70 found similar results in mothers with young children. Poor quality of sleep was associated with increased disinhibited eating compared to participants who rated their sleep as good quality.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…68 A cross-sectional secondary analysis conducted by Blumfield et al 69 in a diverse sample of New York residents found that poor sleep quality was associated with disinhibited eating scores ( B = 0.20; 95% CI, 0.09-0.30, p < .001) and further, sleep quality was indirectly related to increased BMI through higher disinhibition scores ( B = 0.13; 95% CI, 0.06-0.21, p = .001). Eck et al 70 found similar results in mothers with young children. Poor quality of sleep was associated with increased disinhibited eating compared to participants who rated their sleep as good quality.…”
Section: Discussionmentioning
confidence: 66%
“…Poor quality sleep was also associated with increased stress and higher BMI in this population. 70 Based on these findings, sleep is an important factor to consider when planning future study designs.…”
Section: Appreciating the Broader Context: Factors Impacting Postpart...mentioning
confidence: 99%
“…It should be noted that the results presented in this research work include a sample size of 11,698 participants, of whom 61.2% were women. In terms of the study designs, the majority (81%) of the studies included were cross-sectional [ 9 , 12 , 13 , 14 , 19 , 26 , 27 , 28 , 29 , 30 ], while the remaining 19% of the studies were longitudinal [ 17 , 18 , 20 ]. The key findings of all studies included in this systematic review are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the results of the studies included in this systematic review showed that poor sleep quality was significantly associated with emotional eating [ 9 , 12 , 14 , 30 ]. In addition, we observed that other eating behaviors such as external eating [ 14 ], low eating competence [ 24 , 31 ], greater hunger [ 19 ], disinhibited eating behaviors [ 9 , 19 , 30 ], and higher cognitive restraint [ 9 , 26 ] were significantly associated with poor sleep quality.…”
Section: Resultsmentioning
confidence: 99%
“…Health-compromising behaviors are more common among individuals living with stress, depression, and anxiety [ 38 , 39 , 40 , 41 , 42 , 43 ]. For instance, women with greater stress, depression, and/or anxiety are likely to consume less fruits and vegetables, eat more fatty and sugary foods, engage in more emotional eating, drink more alcohol, get less exercise, and have a poorer sleep quality [ 38 , 43 , 44 , 45 , 46 , 47 , 48 ]. These unhealthy behaviors not only have deleterious effects on the health and weight of these women, but they also have the potential to negatively impact others in the family—notably children.…”
Section: Introductionmentioning
confidence: 99%